In silico screening of alleged miRNAs associated with cell competition: an emerging cellular event in cancer. - Patel, M.; Antala, B.; Shrivastava, N. (Cellular & Molecular Biology Letters, 2015)
Cell competition is identified as a crucial phenomenon for cancer and organ development. There is a possibility that microRNAs (miRNAs) may play an important role in the regulation of expression of genes involved in cell competition. In silico screening of miRNAs is an effort to abridge, economize and expedite the experimental approaches to identification of potential miRNAs involved in cell competition, as no study has reported involvement of miRNAs in cell competition to date. In this study, we used multiple screening steps as follows: (i) selection of cell competition related genes of Drosophila through a literature survey; (ii) homology study of selected cell competition related genes; (iii) identification of miRNAs that target conserved cell competitionrelated genes through prediction tools; (iv) sequence conservation analysis of identified miRNAs with human genome; (v) identification of conserved cell competition miRNAs using their expression profiles and exploration of roles of their homologous human miRNAs. This study led to the identification of nine potential cell competition miRNAs in the Drosophila genome. Importantly, eighteen human homologs of these nine potential Drosophila miRNAs are well reported for their involvement in different types of cancers. This confirms their probable involvement in cell competition as well, because cell competition is well justified for its involvement in cancer initiation and maintenance.